Chemical heat derived from rocket-borne WADIS-2 experiment - Grygalashvyly, Mykhaylo; Strelnikov, Boris; Strelnikova, Irina; Rapp, Markus; Lübken, Franz-Josef; Schütt, Corinna; Stephan, Claudia; Eberhart, Martin; Löhle, Stefan; Fascoulas, Stefanos (Earth, Planets and Space, 2024)
Chemical heating rates were derived from three of the most signifcant reactions based on the analysis of common volume rocket-borne measurements of temperature, atomic oxygen densities, and neutral air densities. This is one of the frst instances of the retrieval of nighttime chemical heat through the utilization of non-emissive observations of atomic oxygen concentrations, obtained through in situ measurements, performed at the Andøya Space Center (69°N, 16°E) at 01:44:00 UTC on 5 March 2015. Furthermore, we determine the heating efciency for one of the most signifcant reactions of atomic hydrogen with ozone and illustrate the methodology for such calcula‑ tions based on known atomic oxygen and temperature. Subsequently, using ozone values obtained from satellite observations, we retrieved odd-hydrogens and total chemical heat. Finally, we compared the retrieved chemical heat with the heat from turbulent energy dissipation. Our fndings reveal that the vertically averaged chemical heat is greater than the heat from turbulent energy dissipation throughout the entire mesopause region during nocturnal conditions. The heating rates of turbulent energy dissipation may exceed the chemical heating rates only in narrow peaks, several hundred meters wide.